The utility of counterinsurgency in Balochistan (2013-2019) by the Pakistani Security Forces for achieving the safety of the China Pakistan Economic Corridor (CPEC) - Siddiqui, Khurram Shahzad (2020)
This study examines the utility of the Pakistani Army’s Counterinsurgency (COIN) Strategy (2013-2019) in the eradication of perceived threats facing the China-Pakistan Economic Corridor (CPEC) in Balochistan during the ongoing fifth round of insurgency which started in 2006. The year 2013 is a landmark because a MoU for CPEC was signed between Pakistan and China, the same year as the Pakistani Army first promulgated its new counterinsurgency doctrine. This study analyses the institutional learning process of the Pakistani Army, which ultimately resulted in the promulgation of the COIN doctrine and the extent to which the Army adheres to this doctrinal approach in Balochistan. It empirically investigates the efficacy of the COIN strategy in Balochistan after 2013 concerning CPEC security by using David Kilcullen’s ‘three pillars of counterinsurgency model’ as the conceptual framework. The thesis argues that the COIN approach in Balochistan significantly changed after conceptualising the doctrine, especially from 2016 onwards, from ‘butcher and bolt’ to the inclusion of critical components like political primacy, affect-based and focused use of force, winning ‘hearts and minds’ and rules of engagement. As a result, there was a marked reduction in violence, fatalities and an increased number of insurgent surrenders. This thesis concludes that the Pakistani Army has largely controlled the insurgency in Balochistan, but at the same time, the reduction of tangible support to the insurgents through the porous borders and an effective strategy to break the nexus of the Islamic State of Khorasan (ISK) in Balochistan is urgently required to end the insurgency and ensure CPEC’s security. Key Words: Belt and Road Initiative (BRI), China Pakistan Economic Corridor (CPEC), Balochistan, Insurgency, Security, Counterinsurgency (COIN)